The Causes and Effects of Tropical Deforestation - Leslie Campbell (AGRICA, 2011)
Tropical rainforest deforestation is a major problem in many tropical regions and can have major impacts on system ecology and long term soil productivity. This paper examines the trend of increased colonization of tropical rainforest regions and the resulting effects on long term natural system productivity in these areas. It also explores the impact of conventional agricultural practices, the majority of which were developed in temperate climates, when employed in a tropical context. International trends in the consumption of imported tropical wood and rainforest products are also suggested as a major culprit for increased tropical deforestation. Reduction in international rainforest product consumption and greater awareness on the part of Western consumers as to the impacts of tropical deforestation are suggested as potential solutions to reduce this problem.